2018
DOI: 10.1016/j.juro.2018.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Can Renal and Bladder Ultrasound Replace Computerized Tomography Urogram in Patients Investigated for Microscopic Hematuria?

Abstract: PurposeComputerized tomography urogram is recommended when investigating patients with hematuria. We determined the incidence of urinary tract cancer and compared the diagnostic accuracy of computerized tomography urogram to that of renal and bladder ultrasound for identifying urinary tract cancer.Materials and MethodsThe DETECT (Detecting Bladder Cancer Using the UroMark Test) I study is a prospective observational study recruiting patients 18 years old or older following presentation with macroscopic or micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 22 publications
1
64
1
1
Order By: Relevance
“…Under ideal conditions, CTU has been shown to achieve a sensitivity of 95% and an NPV of 98%, suggesting that CTU can be used as a form of triage to refer patients directly for rigid cystoscopy where transurethral resection of bladder tumour can be performed, bypassing the need for flexible cystoscopy [30]. While we did not find such a high sensitivity and NPV for both CTU and RBUS for the detection of cancer in our patient cohort, we found that the combination of urinary cytology with imaging resulted in an improved sensitivity for the detection of cancer, but this improvement was not sufficient to replace cystoscopy [12].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Under ideal conditions, CTU has been shown to achieve a sensitivity of 95% and an NPV of 98%, suggesting that CTU can be used as a form of triage to refer patients directly for rigid cystoscopy where transurethral resection of bladder tumour can be performed, bypassing the need for flexible cystoscopy [30]. While we did not find such a high sensitivity and NPV for both CTU and RBUS for the detection of cancer in our patient cohort, we found that the combination of urinary cytology with imaging resulted in an improved sensitivity for the detection of cancer, but this improvement was not sufficient to replace cystoscopy [12].…”
Section: Discussioncontrasting
confidence: 59%
“…The combination of urinary cytology with CTU (sensitivity: 92.3, specificity: 94.9%) was superior to urinary cytology with RBUS (sensitivity: 66.7%, specificity: 96.7%). By comparison, CTU alone achieved a diagnostic performance of sensitivity 80.5%, specificity 97.0%, PPV 79.3% and NPV 97.2%, while RBUS had a sensitivity of 50.7%, a specificity of 99.3%, a PPV 84.3% and an NPV of 96.5% .…”
Section: Resultsmentioning
confidence: 91%
“…The gold standard test for investigation of the upper urinary tract is uro-tomography, but in times when we need to consider the use of resources, ultrasound could potentially be used since many imaging services are overloaded due to the frequent indication of thoracic CTs for the diagnosis and follow-up of patients with Sars-Cov-2. These data are extrapolations from recent evidence that ultrasound could replace tomography in the investigation of microscopic hematuria (14). However, once the outbreak is resolved or if the resource is available, uro-tomography should be performed.…”
Section: In Cases Of Patients With Hematuriamentioning
confidence: 67%
“…In all other cases, even if there is urinary retention, we recommend postponing the procedure. If necessary, indwelling urinary catheter placement or percutaneous cystostomy with local anesthesia are indicated for preservation of renal function (13,14).…”
Section: In Cases Of Patients With Benign Prostatic Hyperplasiamentioning
confidence: 99%
“…Nevertheless, patients were psychologically affected particularly between the period of initial cancer diagnosis after flexible cystoscopy and TURBT. This interval represents a period of great uncertainty, where patients are often told of a diagnosis of cancer given the high positive predictive value of cystoscopy but are not informed of disease prognosis given the lack of histopathology [15]. While the implementation of the '2-week wait' pathway in the UK has reduced the time from primary care referral to urology consultation for the investigation of haematuria and diagnosis of bladder cancer, the time to treatment has not reduced [16].…”
Section: Discussionmentioning
confidence: 99%